SOROSITE, CU(SN,SB), A NEW MINERAL FROM THE BAIMKA PLACER DEPOSIT, WESTERN CHUKOTKA, RUSSIAN FAR EAST - Barkov A.Y.; Laajoki K.V.O.; Gornostayev S.S.; Pakhomovskii Y.A.; Men'shikov Y.P. (My University, 1998)
Sorosite, ideally Cu(Sn,Sb), is a new mineral species from the Baimka gold-platinum-group mineral placer deposit, Chukotka, Russian Far East. It occurs as large subhedral to euhedral crystals (0.1-0.4 mm in length), hexagonal in cross section, minute crystals (< or =15 mu m, also hexagonal), and anhedral grains. Sorosite forms inclusions in Sb-bearing native tin, is often intergrown with stistaite (Sn (sub 1.12-1.13) Sb (sub 0.87-0.88) ) and occurs with herzenbergite (SnS), native lead, and trace cassiterite. Sorosite is brittle with a microhardness VHN (sub 40.50) = 443.7 kg/mm 2 (n = 3). No cleavage is observed. In reflected light, the large crystals are nearly white with a pinkish tint, whereas the microcrystals show a pronounced pinkish tint. Bireflectance is variable. The average of nine electron microprobe analyses gave Cu 35.33, Fe 1.18, Sn 58.18, and Sb 4.77, sum 99.46 wt%, corresponding to (Cu (sub 1.00) Fe (sub 0.04) ) (sub Sigma 1.04) (Sn (sub 0.89) Sb (sub 0.07) ) (sub Sigma 0.96) . The powder pattern is close to those of natural Cu(Sn,Sb) and synthetic eta -Cu 6 Sn 5 ; it was indexed for a hexagonal cell, with a = 4.217(4) Aa, c = 5.120(6) Aa, and V = 78.85 Aa 3 . For Z = 2, the calculated density is 7.6 g/cm 3 . The strongest lines in the pattern are at 2.970 (011), 2.112 (110), and 2.094 Aa (012). The sorosite-bearing mineral assemblage apparently formed under low f O2 and f S2 conditions.